Pure bio-based flexible sensing material as well as preparation method and application thereof
By combining Tempo oxidized nanocellulose, bisaldehyde modified cassava starch and gelatin, and immersing it in Fe3+ salt solution, flexible gel sensing materials are constructed, which solves the problems of difficult sensor recycling, poor mechanical properties and high cost, and achieves high mechanical properties and high sensitivity sensing effects, and has biodegradable properties and low cost.
Patent Information
- Application Number
- CN202510037278.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-01-09
AI Technical Summary
Existing sensors are difficult to degrade after recycling, poor mechanical performance and high cost.
Flexible gel sensing material is constructed by combining gel Tempo oxidized nanocellulose with bisaldehyde modified tapioca starch and gelatin and immersing it in Fe3+ salt solution.
It achieves high mechanical properties and high sensitivity sensing properties, and at the same time, since the material is purely bio-based, it has biodegradable properties and low cost.
Smart Images

Figure CN119899413A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of sensor technology, and in particular relates to a pure bio-based flexible sensor material and a preparation method and application thereof. Background Art
[0002] Flexible hydrogel sensors are widely used in wearable devices, health monitoring, artificial electronic skin and other fields. However, the characteristics of flexible hydrogel sensors such as rapid responsiveness, significant sensing stability, incomplete recyclability, green environmental protection, and low cost still face huge challenges. Chinese patent CN118580425A discloses a hydrophobic associating hydrogel based on high-amylose corn starch, a preparation method and an application thereof. High-amylose corn starch is mixed with imidazole ionic liquid to prepare a hydrophobic associating hydrogel, and its tensile stress only reaches 70KPa, and the main part of the gel material is still a petroleum-based material. In addition, there is a document that discloses the preparation of a gel by compounding dialdehyde starch with gelatin, and its compressive stress is only 0.8MPa when the compressive strain is 80%. (Tianqi C, Yuxue S, Yue W, et al. Mechanical, microstructural, and rheological characterization of gelatin-dialdehyde starch hydrogels constructed by dual dynamic crosslinking[J]. LWT, 2022, 161).
[0003] In addition, since petroleum-based flexible sensors are non-degradable and cannot be recycled under natural conditions, the large amount of electronic waste generated after disposal will seriously threaten the environment and ecology, which is not conducive to green sustainable development. At the same time, many conductive hydrogels have poor mechanical properties and will inevitably be damaged and destroyed during deformation in application scenarios. Therefore, driven by the two major issues of environment and application, there is an urgent need to develop a pure bio-based conductive hydrogel strain sensor with excellent mechanical properties, stable sensing, biodegradability, and recyclability. Summary of the invention
[0004] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a pure bio-based flexible sensing material and a preparation method and application thereof, mainly to solve the practical problems that the existing sensors are difficult to degrade after recycling, have poor mechanical properties and high costs.
[0005] In order to achieve the above object, the present invention is implemented through the following technical solutions:
[0006] In a first aspect, the present invention provides a method for preparing a pure bio-based flexible sensing material, comprising the following steps:
[0007] (1) dispersing gel-state Tempo oxidized nanocellulose in an aqueous solution, adding dialdehyde-modified cassava starch thereto, heating to gelatinize it, and ultrasonically dispersing it to obtain liquid A;
[0008] (2) Compounding Liquid A and an aqueous solution of gelatin, stirring and dispersing;
[0009] (3) Pour the solution obtained in step (2) into a mold, refrigerate, and immerse the gel in Fe 3+ Put it in salt solution, cool and solidify to get it.
[0010] Preferably, in step (1), the heating temperature is 70-90° C. and the heating time is 30-60 min.
[0011] Preferably, in step (2), the weight volume fraction of gelatin in water is 8-12 wt %.
[0012] Preferably, in step (2), the mass ratio of liquid A to the aqueous gelatin solution is (0.6-1.2):10.
[0013] Preferably, in step (3), the Fe 3+ The salt solution is selected from one or more of FeCl3 solution, Fe2(SO4)3 solution and FePO4 solution.
[0014] Preferably, the Fe in step (3) 3+ The salt solution is preferably a FeCl3 solution with a concentration of 0.02-0.1 mol / L.
[0015] Further preferably, in step (3), the concentration of the FeCl3 solution is 0.06 mol / L, the immersion time is 24 h, and the immersion temperature is 4°C.
[0016] Preferably, in step (3), the immersion time is 24-48 hours and the immersion temperature is 2-4°C.
[0017] Preferably, in step (3), the refrigeration is refrigerated at 2-4°C for 24-48 hours; and the cooling and solidification temperature is 2-5°C.
[0018] In some embodiments, the aqueous, solution phase is deionized water.
[0019] In some embodiments, the nanocellulose is Tempo-oxidized nanocellulose.
[0020] Cassava starch is a good viscous material and is easy to modify. Tempo oxidized nanocellulose, gelatin aqueous solution and dialdehyde-modified cassava starch are compounded and then immersed in FeCl3 solution to prepare flexible sensor materials. Dialdehyde-modified cassava starch forms dynamic covalent bonds with amino groups in gelatin to improve the mechanical properties of the flexible sensor, while FeCl3 forms coordination bonds with hydroxyl groups in Tempo oxidized nanocellulose, further improving the mechanical properties of the flexible sensor. At the same time, FeCl3 gives the gel good sensing properties.
[0021] Furthermore, the flexible sensing material of the present invention can improve the mechanical properties of the gel and achieve high-sensitivity sensing performance.
[0022] Flexible sensing materials can realize the regulatory design of gel networks, making the sensing materials have fast response and high sensitivity.
[0023] Since dialdehyde-modified cassava starch is biodegradable and non-toxic, the application of dialdehyde-modified cassava starch in the field of flexible sensors provides the possibility for the high-value utilization of cassava starch and broadens the application field of cassava starch.
[0024] The dialdehyde modified cassava starch of the present invention is prepared by oxidation reaction of cassava starch and sodium periodate under acidic conditions. Specifically, cassava starch with a concentration of 6-12wt% and sodium periodate are mixed in a mass ratio of 1:(0.2-1.5), and oxidation reaction is carried out in the dark at a pH of 3.5-4, the reaction temperature is 35-40°C, and the reaction time is 4-6h.
[0025] Preferably, the mass ratio of sodium periodate to cassava starch is (0.2-1.5):1, the concentration of cassava starch is 6-12wt%, the pH of the solution is adjusted to 3.5, the reaction temperature is 35°C, the reaction time is 4h, and the reaction is carried out in the dark.
[0026] Further preferably, the mass ratio of sodium periodate to tapioca starch is 1.5:1.
[0027] In a second aspect, the present invention provides a pure bio-based flexible sensing material prepared by the above-mentioned preparation method.
[0028] In a third aspect, the present invention provides the use of the pure bio-based flexible sensing material in the preparation of flexible wearable sensors and / or health detection sensing materials.
[0029] The beneficial effects achieved by one or more embodiments of the present invention are as follows:
[0030] (1) The dialdehyde-modified cassava starch prepared by the present invention is used as a raw material, compounded with Tempo oxidized nanocellulose and gelatin to form a gel solution, and then immersed in Fe3+ Construction of flexible gel sensing material in salt solution, Fe 3+ Fe in salt solution 3+ Tempo oxidation of OH in nanocellulose - Form a coordination structure that can bind Fe 3+ It is fixed in the gel network and improves the mechanical strength of the gel, making the flexible gel material have a wider range of application scenarios in sensing.
[0031] (2) The preparation process of the dialdehyde-modified cassava starch provided by the present invention is simple, the reaction conditions are mild, and it is suitable for large-scale application.
[0032] (3) The pure bio-based flexible sensing material prepared by the method of the present invention has excellent mechanical strength and good electrical conductivity, and can achieve high-sensitivity sensing performance. When the gel is immersed in a FeCl3 solution with a concentration of 0.06 mol / L, the tensile stress of the gel is 201.4 KPa, the tensile strain is 151.1%, the compressive stress is 5376.43 KPa, and the compressive strain is 93.51%. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 It is a tensile performance diagram of the flexible sensing gel material immersed in 0.02-0.1 mol / L FeCl3 solution of Comparative Example 2 and Examples 5, 6, 7, 8 and 9.
[0034] Figure 2 It is a compression performance diagram of the flexible sensing gel material immersed in 0.02-0.1 mol / L FeCl3 solution of Comparative Example 2 and Examples 5, 6, 7, 8 and 9.
[0035] Figure 3 This is a diagram of the tensile properties of the gel material of Comparative Example 1.
[0036] Figure 4 This is a compression performance diagram of the gel material of Comparative Example 1. DETAILED DESCRIPTION
[0037] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0038] The present invention has no special restrictions on the type and source of the gelatin raw material used. Taking pig bone gelatin as an example, pure gelatin gel is a light yellow gel with a tensile stress of 12 KPa, a tensile strain of 58%, a compressive stress of 164.47 KPa, and a compressive strain of 78.5%.
[0039] Comparative Example 1
[0040] (1) Weigh 1 g of absolutely dry cassava starch without oxidation treatment;
[0041] (2) Weighing 5.76 g of gel-state Tempo oxidized nanocellulose, emulsifying and breaking it up at a concentration of 0.5% for 5 min at 15000 rpm;
[0042] (3) compounding the cassava starch of step (1) and the Tempo oxidized nanocellulose treated in step (2) at a ratio of 1:0.3, gelatinizing at 80° C. and 300 rpm for 30 min, and then sonicating for 5 min;
[0043] (4) Weigh 10 g of absolutely dry gelatin and dissolve it in 30 g of water at 45°C under ultrasonication for 5 min;
[0044] (5) compounding the liquid obtained in step (3) with the liquid obtained in step (4) so that the weight volume fraction of gelatin in water is 10 wt %;
[0045] (6) dispersing the solution obtained in step (5) in a water bath at 65°C and 300 rpm;
[0046] (7) pouring the solution obtained in step (6) into a mold and placing it in a 4°C environment to cool and mold for 24 hours;
[0047] (8) The gel obtained in step (7) was immersed in a 0.06 mol / L FeCl3 solution for 24 h to obtain a flexible sensing gel.
[0048] like Figure 3 and Figure 4 As shown: the obtained flexible sensing gel has a tensile stress of 17.7 KPa, a tensile strain of 36.5%, a compressive stress of 207.1 KPa, and a compressive strain of 67.1%.
[0049] Example 1
[0050] (1) Weigh 2.0 g of NaIO4 and dissolve it in 50 ml of distilled water. Then slowly add 5 g of cassava starch to the NaIO4 solution, and adjust the pH value of the mixture to 3.5 by adding 1 mol / L hydrochloric acid. The oxidation reaction is carried out at 35°C in the dark for 4 h. The reaction product is washed with distilled water and centrifuged 4 times, and then freeze-dried to obtain dialdehyde-modified cassava starch No. 1;
[0051] (2) Weigh 5.76 g of gel-state Tempo oxidized nanocellulose and emulsify it at a concentration of 0.5% for 5 min at 15,000 rpm;
[0052] (3) compounding the No. 1 dialdehyde-modified cassava starch obtained in step (1) and the Tempo-oxidized nanocellulose treated in step (2) in a ratio of 1:0.3, gelatinizing at 80° C. and 300 rpm for 30 min, and then sonicating for 5 min;
[0053] (4) Weigh 10 g of absolutely dry gelatin and dissolve it in 30 g of water at 45°C under ultrasonication for 5 min;
[0054] (5) compounding the liquid obtained in step (3) with the liquid obtained in step (4) so that the weight volume fraction of gelatin in water is 10 wt %;
[0055] (6) dispersing the solution obtained in step (5) in a water bath at 65°C and 300 rpm;
[0056] (7) pouring the solution obtained in step (6) into a mold and placing it in a 4°C environment to cool and mold for 24 hours;
[0057] (8) The gel obtained in step (7) was immersed in a 0.06 mol / L FeCl3 solution for 24 h to obtain a flexible sensing gel.
[0058] Results: The obtained flexible sensing gel had a tensile stress of 23.6 KPa, a tensile strain of 74.9%, a compressive stress of 1043.87 KPa, a compressive strain of 90.26%, and an ionic conductivity of 0.57×10 -2 Sm -1 .
[0059] Example 2
[0060] (1) Weigh 4.0 g of NaIO4 and dissolve it in 50 ml of distilled water. Then slowly add 5 g of cassava starch to the NaIO4 solution, and adjust the pH value of the mixture to 3.5 by adding 1 mol / L hydrochloric acid. The oxidation reaction is carried out at 35°C in the dark for 4 h. The reaction product is washed with distilled water and centrifuged 4 times, and then freeze-dried to obtain No. 2 dialdehyde-modified cassava starch;
[0061] (2) Weigh 5.76 g of gel-state Tempo oxidized nanocellulose and emulsify it at a concentration of 0.5% for 5 min at 15,000 rpm;
[0062] (3) compounding the No. 2 dialdehyde modified cassava starch obtained in step (1) with the Tempo oxidized nanocellulose treated in step (2) in a ratio of 1:0.3, gelatinizing at 80° C. and 300 rpm for 30 min, and then sonicating for 5 min;
[0063] (4) Weigh 10 g of absolutely dry gelatin and dissolve it in 30 g of water at 45°C under ultrasonication for 5 min;
[0064] (5) compounding the liquid obtained in step (3) with the liquid obtained in step (4) so that the weight volume fraction of gelatin in water is 10 wt %;
[0065] (6) dispersing the solution obtained in step (5) in a water bath at 65°C and 300 rpm;
[0066] (7) pouring the solution obtained in step (6) into a mold and placing it in a 4°C environment to cool and mold for 24 hours;
[0067] (8) The gel obtained in step (7) was immersed in a 0.06 mol / L FeCl3 solution for 24 h to obtain a flexible sensing gel.
[0068] Results: The obtained flexible sensing gel had a tensile stress of 57.9 KPa, a tensile strain of 57.9%, a compressive stress of 1287.26 KPa, a compressive strain of 90.47%, and an ionic conductivity of 0.55×10 -2 Sm -1 .
[0069] Example 3
[0070] (1) Weigh 5.0 g of NaIO4 and dissolve it in 50 ml of distilled water. Then slowly add 5 g of cassava starch to the NaIO4 solution, and adjust the pH value of the mixture to 3.5 by adding 1 mol / L hydrochloric acid. The oxidation reaction is carried out at 35°C in the dark for 4 h. The reaction product is washed with distilled water and centrifuged 4 times, and then freeze-dried to obtain No. 3 dialdehyde-modified cassava starch;
[0071] (2) Weigh 5.76 g of gel-state Tempo oxidized nanocellulose and emulsify it at a concentration of 0.5% for 5 min at 15,000 rpm;
[0072] (3) compounding the No. 3 dialdehyde-modified cassava starch obtained in step (1) and the Tempo-oxidized nanocellulose treated in step (2) in a ratio of 1:0.3, gelatinizing at 80° C. and 300 rpm for 30 min, and then sonicating for 5 min;
[0073] (4) Weigh 10 g of absolutely dry gelatin and dissolve it in 30 g of water at 45°C under ultrasonication for 5 min;
[0074] (5) compounding the liquid obtained in step (3) with the liquid obtained in step (4) so that the weight volume fraction of gelatin in water is 10 wt %;
[0075] (6) dispersing the solution obtained in step (5) in a water bath at 65°C and 300 rpm;
[0076] (7) pouring the solution obtained in step (6) into a mold and placing it in a 4°C environment to cool and mold for 24 hours;
[0077] (8) The gel obtained in step (7) was immersed in a 0.06 mol / L FeCl3 solution for 24 h to obtain a flexible sensing gel.
[0078] Results: The obtained flexible sensing gel had a tensile stress of 73.1 KPa, a tensile strain of 55.2%, a compressive stress of 2587 KPa, a compressive strain of 93.64%, and an ionic conductivity of 0.59×10 -2 Sm -1 .
[0079] Example 4
[0080] (1) Weigh 6.0 g of NaIO4 and dissolve it in 50 ml of distilled water. Then slowly add 5 g of cassava starch to the NaIO4 solution, and adjust the pH value of the mixture to 3.5 by adding 1 mol / L hydrochloric acid. The oxidation reaction is carried out at 35°C in the dark for 4 h. The reaction product is washed with distilled water and centrifuged 4 times, and then freeze-dried to obtain No. 4 dialdehyde-modified cassava starch;
[0081] (2) Weigh 5.76 g of gel-state Tempo oxidized nanocellulose and emulsify it at a concentration of 0.5% for 5 min at 15,000 rpm;
[0082] (3) compounding the No. 4 dialdehyde-modified cassava starch obtained in step (1) and the Tempo-oxidized nanocellulose treated in step (2) in a ratio of 1:0.3, gelatinizing at 80° C. and 300 rpm for 30 min, and then sonicating for 5 min;
[0083] (4) Weigh 10 g of absolutely dry gelatin and dissolve it in 30 g of water at 45°C under ultrasonication for 5 min;
[0084] (5) compounding the liquid obtained in step (3) with the liquid obtained in step (4) so that the weight volume fraction of gelatin in water is 10 wt %;
[0085] (6) dispersing the solution obtained in step (5) in a water bath at 65°C and 300 rpm;
[0086] (7) pouring the solution obtained in step (6) into a mold and placing it in a 4°C environment to cool and mold for 24 hours;
[0087] (8) The gel obtained in step (7) was immersed in a 0.06 mol / L FeCl3 solution for 24 h to obtain a flexible sensing gel.
[0088] Results: The obtained flexible sensing gel had a tensile stress of 140.8 KPa, a tensile strain of 74.9%, a compressive stress of 3037.87 KPa, a compressive strain of 92.87%, and an ionic conductivity of 0.56×10 -2 Sm -1 .
[0089] Comparative Example 2
[0090] (1) Weigh 7.5 g of NaIO4 and dissolve it in 50 ml of distilled water. Then slowly add 5 g of cassava starch to the NaIO4 solution, and adjust the pH value of the mixture to 3.5 by adding 1 mol / L hydrochloric acid. The oxidation reaction is carried out at 35°C in the dark for 4 h. The reaction product is washed with distilled water and centrifuged 4 times, and then freeze-dried to obtain No. 5 dialdehyde-modified cassava starch;
[0091] (2) Weigh 5.76 g of gel-state Tempo oxidized nanocellulose and emulsify it at a concentration of 0.5% for 5 min at 15,000 rpm;
[0092] (3) compounding the No. 5 dialdehyde-modified cassava starch obtained in step (1) and the Tempo-oxidized nanocellulose treated in step (2) in a ratio of 1:0.3, gelatinizing at 80° C. and 300 rpm for 30 min, and then sonicating for 5 min;
[0093] (4) Weigh 10 g of absolutely dry gelatin and dissolve it in 30 g of water at 45°C under ultrasonication for 5 min;
[0094] (5) compounding the liquid obtained in step (3) with the liquid obtained in step (4) so that the weight volume fraction of gelatin in water is 10 wt %;
[0095] (6) dispersing the solution obtained in step (5) in a water bath at 65°C and 300 rpm;
[0096] (7) Pour the solution obtained in step (6) into a mold, place it in a 4°C environment and cool it for 24 hours to obtain a flexible sensing gel.
[0097] Results: The tensile stress of the obtained flexible sensing gel was 140.8 KPa, the tensile strain was 74.9%, the compressive stress was 1148.76 KPa, and the compressive strain was 94.37%.
[0098] Example 5
[0099] (1) Weigh 7.5 g of NaIO4 and dissolve it in 50 ml of distilled water. Then slowly add 5 g of cassava starch to the NaIO4 solution, and adjust the pH value of the mixture to 3.5 by adding 1 mol / L hydrochloric acid. The oxidation reaction is carried out at 35°C in the dark for 4 h. The reaction product is washed with distilled water and centrifuged 4 times, and then freeze-dried to obtain No. 5 dialdehyde-modified cassava starch;
[0100] (2) Weigh 5.76 g of gel-state Tempo oxidized nanocellulose and emulsify it at a concentration of 0.5% for 5 min at 15,000 rpm;
[0101] (3) compounding the No. 5 dialdehyde-modified cassava starch obtained in step (1) and the Tempo-oxidized nanocellulose treated in step (2) in a ratio of 1:0.3, gelatinizing at 80° C. and 300 rpm for 30 min, and then sonicating for 5 min;
[0102] (4) Weigh 10 g of absolutely dry gelatin and dissolve it in 30 g of water at 45°C under ultrasonication for 5 min;
[0103] (5) compounding the liquid obtained in step (3) with the liquid obtained in step (4) so that the weight volume fraction of gelatin in water is 10 wt %;
[0104] (6) dispersing the solution obtained in step (5) in a water bath at 65°C and 300 rpm;
[0105] (7) pouring the solution obtained in step (6) into a mold and placing it in a 4°C environment to cool and mold for 24 hours;
[0106] (8) The gel obtained in step (7) was immersed in a 0.02 mol / L FeCl3 solution for 24 h to obtain a flexible sensing gel.
[0107] Results: The tensile stress of the obtained flexible sensing gel was 71.8 KPa, the tensile strain was 77.6%, the compressive stress was 937.30 KPa, and the compressive strain was 94.89%.
[0108] Example 6
[0109] (1) Weigh 7.5 g of NaIO4 and dissolve it in 50 ml of distilled water. Then slowly add 5 g of cassava starch to the NaIO4 solution, and adjust the pH value of the mixture to 3.5 by adding 1 mol / L hydrochloric acid. The oxidation reaction is carried out at 35°C in the dark for 4 h. The reaction product is washed with distilled water and centrifuged 4 times, and then freeze-dried to obtain No. 5 dialdehyde-modified cassava starch;
[0110] (2) Weigh 5.76 g of gel-state Tempo oxidized nanocellulose and emulsify it at a concentration of 0.5% for 5 min at 15,000 rpm;
[0111] (3) compounding the No. 5 dialdehyde-modified cassava starch obtained in step (1) and the Tempo-oxidized nanocellulose treated in step (2) in a ratio of 1:0.3, gelatinizing at 80° C. and 300 rpm for 30 min, and then sonicating for 5 min;
[0112] (4) Weigh 10 g of absolutely dry gelatin and dissolve it in 30 g of water at 45°C under ultrasonication for 5 min;
[0113] (5) compounding the liquid obtained in step (3) with the liquid obtained in step (4) so that the weight volume fraction of gelatin in water is 10 wt %;
[0114] (6) dispersing the solution obtained in step (5) in a water bath at 65°C and 300 rpm;
[0115] (7) pouring the solution obtained in step (6) into a mold and placing it in a 4°C environment to cool and mold for 24 hours;
[0116] (8) The gel obtained in step (7) was immersed in a 0.04 mol / L FeCl3 solution for 24 h to obtain a flexible sensing gel.
[0117] Results: The obtained flexible sensing gel had a tensile stress of 108.9 KPa, a tensile strain of 77.2%, a compressive stress of 1990.27 KPa, a compressive strain of 89.63%, and an ionic conductivity of 0.17×10 -2 Sm -1 .
[0118] Example 7
[0119] (1) Weigh 7.5 g of NaIO4 and dissolve it in 50 ml of distilled water. Then slowly add 5 g of cassava starch to the NaIO4 solution, and adjust the pH value of the mixture to 3.5 by adding 1 mol / L hydrochloric acid. The oxidation reaction is carried out at 35°C in the dark for 4 h. The reaction product is washed with distilled water and centrifuged 4 times, and then freeze-dried to obtain No. 5 dialdehyde-modified cassava starch;
[0120] (2) Weigh 5.76 g of gel-state Tempo oxidized nanocellulose and emulsify it at a concentration of 0.5% for 5 min at 15,000 rpm;
[0121] (3) compounding the No. 5 dialdehyde-modified cassava starch obtained in step (1) and the Tempo-oxidized nanocellulose treated in step (2) in a ratio of 1:0.3, gelatinizing at 80° C. and 300 rpm for 30 min, and then sonicating for 5 min;
[0122] (4) Weigh 10 g of absolutely dry gelatin and dissolve it in 30 g of water at 45°C under ultrasonication for 5 min;
[0123] (5) compounding the liquid obtained in step (3) with the liquid obtained in step (4) so that the weight volume fraction of gelatin in water is 10 wt %;
[0124] (6) dispersing the solution obtained in step (5) in a water bath at 65°C and 300 rpm;
[0125] (7) pouring the solution obtained in step (6) into a mold and placing it in a 4°C environment to cool and mold for 24 hours;
[0126] (8) The gel obtained in step (7) was immersed in a 0.06 mol / L FeCl3 solution for 24 h to obtain a flexible sensing gel.
[0127] Results: The obtained flexible sensing gel had a tensile stress of 201.4 KPa, a tensile strain of 151.1%, a compressive stress of 5376.43 KPa, a compressive strain of 93.51%, and an ionic conductivity of 0.57×10 -2 Sm -1 .
[0128] Example 8
[0129] (1) Weigh 7.5 g of NaIO4 and dissolve it in 50 ml of distilled water. Then slowly add 5 g of cassava starch to the NaIO4 solution, and adjust the pH value of the mixture to 3.5 by adding 1 mol / L hydrochloric acid. The oxidation reaction is carried out at 35°C in the dark for 4 h. The reaction product is washed with distilled water and centrifuged 4 times, and then freeze-dried to obtain No. 5 dialdehyde-modified cassava starch;
[0130] (2) Weigh 5.76 g of gel-state Tempo oxidized nanocellulose and emulsify it at a concentration of 0.5% for 5 min at 15,000 rpm;
[0131] (3) compounding the No. 5 dialdehyde-modified cassava starch obtained in step (1) and the Tempo-oxidized nanocellulose treated in step (2) in a ratio of 1:0.3, gelatinizing at 80° C. and 300 rpm for 30 min, and then sonicating for 5 min;
[0132] (4) Weigh 10 g of absolutely dry gelatin and dissolve it in 30 g of water at 45°C under ultrasonication for 5 min;
[0133] (5) compounding the liquid obtained in step (3) with the liquid obtained in step (4) so that the weight volume fraction of gelatin in water is 10 wt %;
[0134] (6) dispersing the solution obtained in step (5) in a water bath at 65°C and 300 rpm;
[0135] (7) pouring the solution obtained in step (6) into a mold and placing it in a 4°C environment to cool and mold for 24 hours;
[0136] (8) The gel obtained in step (7) was immersed in a 0.08 mol / L FeCl3 solution for 24 h to obtain a flexible sensing gel.
[0137] Results: The obtained flexible sensing gel had a tensile stress of 130.6 KPa, a tensile strain of 97.1%, a compressive stress of 5753.54 KPa, a compressive strain of 86.44%, and an ionic conductivity of 0.73×10 -2 Sm -1 .
[0138] Example 9
[0139] (1) Weigh 7.5 g of NaIO4 and dissolve it in 50 ml of distilled water. Then slowly add 5 g of cassava starch to the NaIO4 solution, and adjust the pH value of the mixture to 3.5 by adding 1 mol / L hydrochloric acid. The oxidation reaction is carried out at 35°C in the dark for 4 h. The reaction product is washed with distilled water and centrifuged 4 times, and then freeze-dried to obtain No. 5 dialdehyde-modified cassava starch;
[0140] (2) Weigh 5.76 g of gel-state Tempo oxidized nanocellulose and emulsify it at a concentration of 0.5% for 5 min at 15,000 rpm;
[0141] (3) compounding the No. 5 dialdehyde-modified cassava starch obtained in step (1) and the Tempo-oxidized nanocellulose treated in step (2) in a ratio of 1:0.3, gelatinizing at 80° C. and 300 rpm for 30 min, and then sonicating for 5 min;
[0142] (4) Weigh 10 g of absolutely dry gelatin and dissolve it in 30 g of water at 45°C under ultrasonication for 5 min;
[0143] (5) compounding the liquid obtained in step (3) with the liquid obtained in step (4) so that the weight volume fraction of gelatin in water is 10 wt %;
[0144] (6) dispersing the solution obtained in step (5) in a water bath at 65°C and 300 rpm;
[0145] (7) pouring the solution obtained in step (6) into a mold and placing it in a 4°C environment to cool and mold for 24 hours;
[0146] (8) The gel obtained in step (7) was immersed in a 0.10 mol / L FeCl3 solution for 24 h to obtain a flexible sensing gel.
[0147] Results: The obtained flexible sensing gel had a tensile stress of 122.8 KPa, a tensile strain of 86.5%, a compressive stress of 3519.72 KPa, a compressive strain of 95.16%, and an ionic conductivity of 0.96×10 -2 Sm -1 .
[0148] Result analysis:
[0149] Figure 1 It is a tensile performance diagram of the flexible sensing gel material immersed in 0.02-0.1 mol / L FeCl3 solution of Comparative Example 2 and Examples 5, 6, 7, 8 and 9. Figure 2 The compression performance diagram of the flexible sensing gel material immersed in 0.02-0.1 mol / L FeCl3 solution of Comparative Example 2, Examples 5, 6, 7, 8, and 9. It can be seen that compared with Comparative Example 2, the tensile and compressive properties of the gel materials obtained in Examples 5 to 9 are greatly improved. 3+ As the concentration increases, the performance of the obtained gel material is significantly enhanced, but 3+ If the concentration is too high, the coordination effect with -COOH will be too strong, causing the gel material structure to expand, affecting the density of the network structure in the gel, and ultimately leading to a decrease in the mechanical properties of the material.
[0150] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a pure bio-based flexible sensing material, characterized in that: The steps include: (1) dispersing gel-state Tempo oxidized nanocellulose in an aqueous solution, adding dialdehyde-modified cassava starch thereto, heating to gelatinize it, and ultrasonically dispersing it to obtain liquid A; (2) Mixing liquid A with the gelatin aqueous solution and stirring to disperse; (3) Pour the solution obtained in step (2) into a mold, refrigerate, and immerse the gel in Fe 3+ In salt solution, cool and solidify to obtain.
2. The method for preparing a pure bio-based flexible sensing material according to claim 1, characterized in that: The dialdehyde-modified cassava starch described in step (1) is prepared by oxidation reaction of cassava starch and sodium periodate under acidic conditions; the specific preparation method is: mixing cassava starch and sodium periodate, and carrying out oxidation reaction under dark conditions and pH 3.5-4, the reaction temperature is 35-40° C., and the reaction time is 4-6 hours.
3. The method for preparing a pure bio-based flexible sensing material according to claim 2, characterized in that: The mass ratio of sodium periodate to cassava starch is (0.2-1.5):1, and the concentration of cassava starch is 6-12wt%.
4. The method for preparing a pure bio-based flexible sensing material according to claim 1, characterized in that: In step (1), the heating temperature is 70-90° C. and the heating time is 30-60 min.
5. The method for preparing a pure bio-based flexible sensing material according to claim 1, characterized in that: In step (2), the weight volume fraction of gelatin in water is 8-12wt%.
6. The method for preparing a pure bio-based flexible sensing material according to claim 1, characterized in that: In step (2), the mass ratio of liquid A to the aqueous gelatin solution is (0.6-1.2):
10.
7. The method for preparing a pure bio-based flexible sensing material according to claim 1, characterized in that: In step (3), the Fe 3+ The salt solution is selected from one or more of FeCl3 solution, Fe2(SO4)3 solution and FePO4 solution.
8. The method for preparing a pure bio-based flexible sensing material according to claim 1, characterized in that: In step (3), the Fe 3+ The salt solution is a FeCl3 solution with a concentration of 0.02-0.1 mol / L; in step (3), the immersion time is 24-48 hours and the immersion temperature is 2-4°C.
9. A pure bio-based flexible sensing material, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 8.
10. Use of a pure bio-based flexible sensing material as described in claim 9 in the preparation of flexible wearable sensors and / or health detection sensing materials.
Citation Information
Patent Citations
Nano-crystalline cellulose / gelatin composite aerogel and application thereof
CN109225077A
Underwater elastic cellulose aerogel and preparation method and application thereof
CN112898625A
Gelatin-based conductive hydrogel with high strength and high additional value as well as preparation method and application of gelatin-based conductive hydrogel
CN114437370A
Computer implemented method for automatically designing a workflow to perform a semiconductor inspection task
KR1020250079886A
Method of producing nanocellulose
US20170306055A1